Treatment of Bartter syndrome. Unsolved issue - Carla Lessa Pena Nascimento; Cecilia Lopes Garcia; Benita Galassi Soares Schvartsman; Maria Helena Vaisbich (Brazilian Society of Pediatrics, 2014)
Objective: To describe the results of a long‐term follow‐up of Bartter syndrome patients treated with different drugs. Method: Patients were diagnosed according to clinical and laboratory data. Treatment protocol was potassium supplementation, sodium, spironolactone, and non‐steroidal anti‐inflammatory drug. Patients who developed proteinuria were converted to angiotensin conversion enzyme inhibitor. The variables evaluated for each drug were Z‐score for weight and stature, proteinuria, creatinine clearance, gastrointestinal complaints, amount of potassium supplementation, serum potassium and bicarbonate levels, and findings of upper digestive endoscopy. Results: 20 patients were included. Follow‐up was 10.1 ± 5.2 years. 17 patients received indomethacin for 5.9 ± 5.3 years; 19 received celecoxib, median of 35 months; and five received enalapril, median of 23 months. During indomethacin, a statistically significant increase was observed in the Z‐score for stature and weight, without a change in the creatinine clearance. Seven of 17 patients had gastrointestinal symptoms, and upper digestive endoscopy evidenced gastritis in three patients and gastric ulcer in four patients. During celecoxib use, a significant increase was detected in the Z‐score for stature and weight and a reduction of hyperfiltration; seven patients presented gastrointestinal symptoms, and upper digestive endoscopy evidenced mild gastritis in three. During enalapril use, no significant changes were observed in the Z‐score for stature, weight and creatinine clearance. The conversion to enalapril resulted in a significant reduction in proteinuria. Conclusion: The authors suggest starting the treatment with celecoxib, and replacing by ACEi if necessary, monitoring the renal function. The safety and efficacy of celecoxib need to be assessed in larger controlled studies.